PENYAJIAN CERITA RAKYAT SORONG “TERJADINYA SUNGAI KOHOIN DI TEMINABUAN” SEBAGAI BAHAN BACAAN SISWA SD - Normawati NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Papua, specially Sorong regency, has a lot of folktale. However, the folktale is not be used yet for children’s literature as learning in the school. Therefore, the research describes the appropriate the structure of Sorong folktale “Terjadinya Sungai Kohoin di Teminabuan” with the development of children intelectual. The source of data is written text that contains of folktale with using descriptive qualitative. The result shows that this folktale appropriates with criteria for assessment of children’s literature, so, it’s worth as  literature for student of Elementary School 7—11 years old.  The suitability can be seen in a simple story by using liniear groove, flat characters which shown in black and white, and the using of vocabulary and simple sentences. Beside that, the folktale of “Terjadinya Sungai Kohoin di Teminabuan” has theme and moral value, namely environment caring and to cooperative that will establish children character.